Wither Fled Lamia?: A Search for Signification - Mark Thomas (Names, 1989)
Abstract The “Perrea” in John Keats's poem “Lamia” has until now remained unidentified by literary scholars. Geographical and orthographical ambiguities cloud the issue, particularly because “Lamia” shows Keats inventing words and spellings. This article traces some of the implications of readings based on several possible candidates before identifying Keats's referent: PerreaChora.